BRST cohomology and nonlocal conserved charges - Berkovits, Nathan [UNESP] (Springer Nature, 2005)
A relation is found between nonlocal conserved charges in string theory and certain ghost-number two states in the BRST cohomology. This provides a simple proof that the nonlocal conserved charges for the superstring in an AdS 5 × S5 background are BRST-invariant in the pure spinor formalism and are κ-symmetric in the Green-Schwarz formalism. © SISSA/ISAS 2005.
Keywords: AdS-CFT and dS-CFT Correspondence; BRST Symmetry